Growth and Morphological Responses of Duckweed to Clonal Fragmentation, Nutrient Availability, and Population Density - Zhang, Li-Min; Jin, Yu; Yao, Si-Mei; Lei, Ning-Fei; Chen, Jin-Song; Zhang, Qian; Yu, Fei-Hai (Frontiers in Plant Science, 2020)
Connected ramets of aquatic clonal plants are susceptible to fragmentation by disturbance. Such clonal fragmentation may interact with nutrient availability and individual density to affect growth and morphology of aquatic clonal plants. We grew the widespread floating clonal plant Spirodela polyrhiza (duckweed) under three levels of population density (low, medium, or high), two levels of nutrient availability (low or high), and two levels of clonal fragmentation (with or without). Clonal fragmentation and high nutrients increased biomass and ramet number, but decreased frond width, frond length, and specific frond area of S. polyrhiza. Increasing population density decreased growth (biomass and ramet number) and frond and root size, and increased frond thickness of individual ramets of S. polyrhiza. The negative effect of population density on growth of S. polyrhiza was greater under high than under low nutrient availability. Furthermore, the negative effect of population density on total mass and frond mass of S. polyrhiza was greater with fragmentation than without. These results suggest that clonal fragmentation, nutrient availability and population density can interact to affect growth and morphology of clonal floating plants. Competition for nutrients and space, rather than light, may be the mechanisms underlying reduced growth of clonal floating plants. As clonal fragmentation can increase biomass and ramet production of S. polyrhiza, disturbance that potentially causes clonal fragmentation cannot be recommended as a measure to limit the spread of clonal floating plants.